KUALITAS SOAL FREDIKSI UJIAN NASIONAL HASIL DIKLAT UJIAN NASIONAL GURU BAHASA INGGRIS MA TAHUN 2019 - ., Sholikin (Balai Diklat Keagamaan Surabaya, 2019)
Evaluation or Exam is an activity that is inseparable from the activity of teaching and learning carried out bythe teacher. Evaluation in the learning process has a very important role because from the evaluation, theteacher will get information about the level of competency of the students, the level of effectiveness of alesson. For this reason teachers need to be given competencies to develop an adequate evaluation tool sothat they can provide the right picture. The focus of this research is 1] How is the effectiveness of testsdestraction developed by Diklat participants ? 2] How is the level of difficulty indext of the test ? 3] Howis the quality of the descrimination index of the test ? This research method uses a Descriptive approach,with the subjects of the study were 35 English Teachers training participants. While the data collectiontechniques used the document, the results of the Prediction Tests developed by the training participantsand it was analyzed by Anates Version 04. The results of the analysis showed that the effectiveness ofdestractions were still not good, beside that there were still too difficult and too easy tests.While theDescrimination Index were more than 50 % of the questions withbad different power.